TERAPI KELOMPOK SUPORTIF ASERTIF MENURUNKAN NILAI PERILAKU KEKERASAN PASIEN SKIZOFRENIA BERDASARKAN MODEL KEPERAWATAN INTERAKSI KING - Khamida, K (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
Violent behavior can endanger ourselves, others and environment. One of the more optimal treatments which is highly needed is the assertive supportive group therapy by using the approach of King’s model of nursing interaction, in which the patient together with his group is asked to give support to do the assertive behavior to each other. The study was purposed to analyze the effects of assertive supportive group therapy on violent behavior done by the Schizophrenic patients based on the King’s interaction nursing model. Method: The design of this study was the pre-post test control group. The population involved the patients with violent behavior hospitalized in the in-patient ward of RSJ Menur Surabaya. The samples of 20 respondents were taken by using simple random sampling technique. The independent variable was the assertive supportive group therapy, whereas the dependent one was violent behavior. Furthermore, the data were collected by filling out the observation sheet. The data were processed by using Paired T-test, Wilcoxon’s Signed Rank Test, and Mann-Whitney’s statistic test. Result: The result of study showed that before receiving this therapy, the average value of violent behavior in the treatment group was 96.1, whereas the average value found in the control group was 75.1. After receiving the assertive supportive group therapy, the average value of violent behavior in the treatment group was 58.4, whereas the average value found in the control group was 54.8. Moreover, the result of statistic test in the treatment group showed that the value difference of violent behavior before and after the treatment was p = 0.005, whereas the value difference found in the control group was p = 0.000, and the effects of the assertive supportive group therapy on violent behavior was p = 0.045. Discussion: The assertive supportive group therapy with King’s model of nursing interaction could decrease the patient’s violent behavior by optimizing the personal system and interpersonally giving support to one another within the group. Therefore, the qualitative study is needed to complete the information about how the assertive supportive group therapy brings some effects to decrease violent behavior